2013
DOI: 10.1179/2042645313y.0000000042
|View full text |Cite
|
Sign up to set email alerts
|

Performance of clear coatings on modified wood exposed to the weather for 2 years in Australia

Abstract: We examine the performance of clear coatings on wood treated to improve its photostability. The treatments tested were: benzoyl chloride; chromic acid; modified PF resins; vinyl benzoate; and primers containing different photostabilisers. Treated panels were finished with clear coatings containing different types/levels of photostabilisers and exposed outdoors in Australia for 2 years. The coatings performed better on treated than untreated panels, except for coatings on panels treated with a primer containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
(28 reference statements)
0
16
0
1
Order By: Relevance
“…This form of failure is quite common although other forms of failure occur. For example, very hard inflexible coatings fail even more quickly by cracking and large-scale delamination of the coating [34]. Clear coated wood products in tropical climates can fail very quickly due to decay of the wood before there is complete failure of the clear coating [10].…”
Section: Mechanisms For the Failure Of Clear Coatings On Woodmentioning
confidence: 99%
See 4 more Smart Citations
“…This form of failure is quite common although other forms of failure occur. For example, very hard inflexible coatings fail even more quickly by cracking and large-scale delamination of the coating [34]. Clear coated wood products in tropical climates can fail very quickly due to decay of the wood before there is complete failure of the clear coating [10].…”
Section: Mechanisms For the Failure Of Clear Coatings On Woodmentioning
confidence: 99%
“…The cracking of the coating containing the binder with the high Tg began after 1 year of exposure while no cracking was observed in the finish containing the binder with a Tg of 10 °C [40]. Vollmer and Evans also observed that a hard inflexible acrylic coating formulated for metals failed far more quickly on wood than more flexible coatings [34]. The relationship between the flexibility of phenolic varnishes and alkyd clear coatings and their durability on wood exposed to the weather was examined by Ashton [39].…”
Section: Coating Flexibilitymentioning
confidence: 99%
See 3 more Smart Citations